The Compliance of Health Workers Doing Five Moments Of Handwashing With The Incidence Of Nosocomial Infections: Literature Review - Zulkarnain, Eva Vera; Muhith, Abdul; Chilyatiz (Chakra Brahmanda Lentera Institute, 2024)
Background: Nosocomial infection is a cross-infection in nurses or patients during hospital treatment. One of the factors that can prevent nosocomial infections is health workers' compliance in carrying out 6 (six) hand washing steps. This literature review aims to determine the relationship between the compliance of health workers washing hands and the incidence of nosocomial infections in hospitals. Methods: The method used in this article is a literature review using the PRISMA Approach. Journal databases from Science Direct, PubMed, and Google Scholar in the 2019-2023 time frame. Keywords